2021
DOI: 10.1007/s00784-021-04167-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonisation during regular daily use of a power-driven water flosser and risk for cross-contamination. Can it be prevented?

Abstract: Objective To assess whether bacterial colonisation in a power-driven water flosser can be prevented. Materials and methods Twenty-four patients undergoing supportive periodontal treatment used 2 power-driven water flossers [Sonicare AirFloss (SAF), AirFloss Ultra (SAFU)] for 12 weeks each as follows: (a) with bottled water (BW); (b) with BW and cleaning the device extra-orally twice per week with chlorhexidine gluconate or (c) essential-oil-based (EO) mout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…In general, all studies included herein reported that PDICTs are indeed safe to use. Nevertheless, recent reports from our group have indicated that liquid‐based PDICTs are unavoidably colonized by oral bacteria, which can be transmitted via the water jet (Bertl, Edlund Johansson, Bruckmann et al, 2021 ; Bertl et al, 2022 ). Contamination of a specific liquid‐based PDICT with Streptococcus mutans was found in >95% of the samples, while periodontal pathogens were detected in 19%–56% of the samples (Bertl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, all studies included herein reported that PDICTs are indeed safe to use. Nevertheless, recent reports from our group have indicated that liquid‐based PDICTs are unavoidably colonized by oral bacteria, which can be transmitted via the water jet (Bertl, Edlund Johansson, Bruckmann et al, 2021 ; Bertl et al, 2022 ). Contamination of a specific liquid‐based PDICT with Streptococcus mutans was found in >95% of the samples, while periodontal pathogens were detected in 19%–56% of the samples (Bertl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent reports from our group have indicated that liquid‐based PDICTs are unavoidably colonized by oral bacteria, which can be transmitted via the water jet (Bertl, Edlund Johansson, Bruckmann et al, 2021 ; Bertl et al, 2022 ). Contamination of a specific liquid‐based PDICT with Streptococcus mutans was found in >95% of the samples, while periodontal pathogens were detected in 19%–56% of the samples (Bertl et al, 2022 ). Based on these reports, the commonly suggested use of the same device within families, with only exchanging the device tip among family members, should be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concerns about bacterial colonization and the risk of cross-contamination have been raised during regular daily use of power-driven WFs [ 53 ]. Dental irrigators can cause transient bacteremia, with incidence correlated to oral hygiene and periodontal disease [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…A major issue, as highlighted in our literature review, lies in the limited comparative evidence, and lack of systematic reviews regarding the efficacy of WFs in the management of periodontal disease. There have been studies, which show that there is little to no effect on the composition of subgingival plaque and reducing periodontal pockets [51,52] Furthermore, concerns about bacterial colonization and the risk of cross-contamination have been raised during regular daily use of power-driven WFs [53]. Dental irrigators can cause transient bacteremia, with incidence correlated to oral hygiene and periodontal disease [54].…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…ntimikrobiyal, antiinflamatuvar, antiseptik, antifungal ve antikaryojenik özelliklerinden dolayı diş hekimliğinde diş macunu, jel ve gargara formülasyonlarda yer alan esansiyel yağların diş ve diş eti hastalıklarında önemli terapötik etkinliğe sahip olduğunu gösteren çalışmalar literatürde yer almaktadır. Günümüzde esansiyel yağların periodontal hastalıklar üzerindeki teröpatik etklerinin daha iyi anlaşılması ve esansiyel yağ bazlı yeni formülasyonların geliştirilmesi adına in vitro,in vivo çalışmalar ve hayvan deneyleri yapılmaya devam edilmektedir (44)(45)(46)(47)(48)(49)(50). Tüm bu bilgiler ışığında esansiyel yağların periodontal hastalıkların tedavisinde kullanımı araştırmaya hala açık olan bir konudur.…”
Section: Sonucaunclassified